Beyond boundaries: how autonomy and technology promote work engagement and well-being in remote workers - Olivo, Ilaria; Ghezzi, Valerio; Marzocchi, Ivan; Fusco, Luigi; Spinella, Francesca; Isolani, Stefano; Ronchetti, Matteo; Ghelli, Monica; Russo, Simone; Barbaranelli, Claudio; Persechino, Benedetta; Iavicoli, Sergio (Frontiers in Public Health, 2025)
This longitudinal investigation explores the role of technology as resource and job autonomy in influencing remote workers’ engagement and private lives during the transition to remote work, spurred by the COVID-19 pandemic. Data of 194 employees of the Italian Public Administration were collected across three time points: pre-remote work (T0, December 2018), limited remote work (T1, December 2019), and full-time remote work during the pandemic (T2, July 2020). The findings showed that job autonomy and technology as resources enhance work engagement, while engaged workers develop a more positive perception of technological tools. Notably, engagement did not predict autonomy, likely due to contextual constraints such as the abrupt transition to full-time remote work. The perception of technology as a resource significantly improved private life outcomes. These insights underline the critical role of tailored technological support and organizational policies in fostering a productive and balanced remote work environment, enabling organizations to better meet the needs of their workforce.